Real-time estimation of the pressure in the wheel cylinder with a hydraulic control unit in the vehicle braking control system based on the extended Kalman filter. (September 2017) - Jiang, Guirong; Miao, Xiaolu; Wang, Yuehui; Chen, Jie; Li, Dalong; Liu, Lifu; Muhammad, Fahad
The pressure in the wheel cylinder plays an important role in the anti-lock braking system, but direct measurement usually needs expensive sensors. Therefore, estimation of the pressure in the wheel cylinder is of great significance to optimize the algorithm of the anti-lock braking system. There are two commonly used estimation methods: one is based on the hydraulic model, and the other is based on the equation for the tyre dynamics. Both of these, however, suffer from inadequacies. The former method is sensitive to the accuracy of the model in practical applications, and an accumulated error appears if some parameters of the process are not sufficiently accurate. In the latter method the pressure in the wheel cylinder is calculated for each cycle but, when the vehicle is running, the fluctuations in the deceleration are relatively large. To estimate the pressure more accurately, a novel method is proposed in this paper, which combines these two methods on the basis of the extended Kalman filter. The method can compensate for the inadequacies of the two methods mentioned above by using the variation in the wheel speed as the observation variable to modify the hydraulic model. It can decrease its sensitivity to the accuracy of the hydraulic model and improve the accuracy of the estimated magnitude of the pressure. The estimated results are compared with the real values which are obtained by using a pressure sensor on a typical low-friction road and on an asphalt road; in addition, the effectiveness of the novel method is validated by hardware-in-the-loop tests and vehicle tests. The results show that the proposed method can provide an accurate estimation of the pressure in the wheel cylinder during hydraulic control of the anti-lock braking system or any other brake control system.